Acoustical modelling of cleft palate - KACPROWSKI, Janusz; MIKIEL, Władysław; SZEWCZYK, Alicja (Archives of Acoustics, 1976)
The subject of the present paper is the theoretical analysis of the influence of cleft palate upon the transmission characteristics of the vocal tract in glottal excitation. Starting with a simplified anatomical model of the human vocal system and using the graphical analysis method, we determined the pole-zero distribution of the transfer function K (w) which describes the formant-anti-formant structure of oral vowels nasalized due to the shunting effect of the nasal channel. The experimental investigations, performed with a specially designed and constructed acoustic analogue model of the speech organ in 5:1 dimension scale and, consequently, in 1:5 frequency scale, confirmed the validity of the assumptions and the results of the theoretical analysis. It was proved that the spectral analysis of oral vowels, in pathological and post-operative states of cleft palate, affords information which specifies the changes of the acoustic structure of the speech organ due to anatomical disorders. This information offers new facilities in objective phoniatric diagnostics as well as in the control of the process of medical rehabilitation in cleft palate cases, by means of acoustical methods based on the spectral analysis of the speech signal.